A rare carbapenem-resistant hypervirulent K1/ST1265 Klebsiella pneumoniae with an untypeable blaKPC-harboured conjugative plasmid. (September 2020) - Li, Cuidan; Ma, Guannan; Yang, Tingting; Wen, Xiaoyu; Qin, Chuan; Yue, Liya; Jia, Xinmiao; Shen, Yicheng; Lu, Dandan; Wang, Lifeng; Shen, Dingxia; Chen, Fei
Highlights: A rare carbapenem-resistant hypervirulent K1/ST1265 Klebsiella pneumoniae was analyzed. The strain carries a bla KPC -harboured conjugative plasmid and a pLVPK-like virulent plasmid. CR-HvKP strain could be evolved from various types of HvKP strains. R-M system on plasmids may protect the plasmids from cleavage. Pernicious CR-HvKP strains pose serious threats to public health. Abstract: Objective: We investigated the pathogenesis of a patient with severe acute pancreatitis by comprehensively analysing a rare carbapenem-resistant hypervirulent K1/ST1265 Klebsiella pneumoniae (CR-HvKP) strain. Methods: We conducted virulence and multidrug-resistance phenotypic characterization and identified a CR-HvKP strain from the patient. It was subjected to Pacbio sequencing, and subsequent analysis of virulence, resistance genes and mobile genetic elements. Results: We described the phenotype and genotype of a rare CR-HvKP strain with an untypeable bla KPC -harboured conjugative plasmid and a pLVPK-like virulent plasmid. Resistance gene analysis showed that the untypeable bla KPC-2 -harboured plasmid was formed by IS 26 -mediated recombination of bla KPC -embedded transposon Tn 6500 into pCN061p4 from Escherichia coli . Interestingly, it had an R-M system that might protect plasmid from cleavage. This may facilitate the stabilization of plasmids in bacteria in the event of missing CR-plasmid during transmission. Virulence gene analysis indicated 78 virulence genes on the genome, including 67 on the chromosome (37 in high-pathogenic island) and 11 on the pLVPK-like virulence plasmid (harbouring rmpA / rmpA2 ). Further phylogenetic analysis revealed that the CR-HvKP evolved from HvKP through acquiring an antimicrobial-resistance plasmid. Conclusion: Our research, to our knowledge, first reported a ST1265/K1 CR-HvKP strain with an untypeable bla KPC -harboured plasmid. The trend that HvKP could evolve into CR-HvKP by obtaining stabilized/conjugative bla KPC -carrying plasmids is a considerable threat to public health and should be closely supervised.